Law of Usury (RIBA) According to Masyarakat Tanpa Riba (MTR): Perceptions, Attitudes, and Movements - Al-Hakim, Sofian; Witro, Doli; Nurjaman, Muhamad Izazi (Asy-Syari'ah, 2024)
Abstract: After the merger, three banks under State-Owned Enterprises (BUMN), namely BNI Syariah, BRI Syariah, and Bank Syariah Mandiri, became Bank Syariah Indonesia (BSI), opening opportunities for the development of Islamic financial institutions in Indonesia. However, according to the Masyarakat Tanpa Riba (Society Without Riba) (MTR), Islamic banks are not much different from conventional banks (BK). Therefore, the focus of this article is the law of usury in the view of the MTR, which is seen in three aspects, namely, the perception, attitude, and movement of the MTR. This paper aims to determine the law of usury from the view of the MTR. This article uses a qualitative research method, which is field research. Data collection techniques used are observation, interviews, and documents. The data analysis technique in this paper uses data condensation, data presentation, and conclusion. The study results show that the MTR is an anti-usury community. MTR can be categorised as a textualist and rigid group (mutasyadidun). The rigid MTR method often implies that Islamic economic development is static and monolithic. The existence of the MTR will be productive if it is read not as a threat but as an auto-criticism against Sharia financial practices that are not yet perfect, highlighting the potential impact of the MTR's perspective on Islamic financial practices.